FRI0166 Ethnicity is Associated with Biologic Treatment Persistence in Rheumatoid Arthritis. (9th June 2015) - Kumar, K.; Sahbudin, I.; Filer, A.; Buckley, C.D.; Raza, K.; Stack, R.; Nightingale, P.; Deeming, A.; Situnayake, D.; de Pablo, P.
Abstract : Background: Understanding the persistence of biologic treatment in different ethnic groups is important for efficient healthcare delivery. We previously reported that patients with Rheumatoid Arthritis (RA) from South Asian background had high level of side effect concerns about conventional DMARDs (cDMARDs) compared with patients of White British origin. These concerns may have an impact on treatment persistence; however, there is little data on biologic DMARDs (bDMARDs) treatment persistence among different ethnic groups. Objectives: To investigate biologic DMARDs treatment persistence and reasons for switching among patients with RA from South Asian and White British background. Methods: This service evaluation project identified 336 patients with active RA diagnosed by Consultant Rheumatologists at the Sandwell and West Birmingham Hospitals NHS Trust, UK. All patients were commenced on bDMARDs according to NICE guidelines between May 2001 and August 2013. Frequency of loss of efficacy, number of bDMARDs switches and treatment duration for each bDMARD, were compared between South Asian and White British patients. Loss of efficacy was defined as a drop of DAS-28 score ≤1.2 after at least three months of therapy, or by loss of efficacy in the opinion of the treating physician. Results: The sample included 77 (23%) South Asian and 259 (77%) White British patients with active RA commencing bDMARDs therapy. The frequency of side effects was similar in both groups. Loss of efficacy was more common among South Asian compared with White British patients (65.6% vs. 52.2%; p=0.03). Regarding the number of biologic DMARDs switches, South Asian patients switched bDMARDs more frequently compared to their White British counterparts (South Asian vs White British; one switch: 24.7% vs 21.6%; two switches: 19.5% vs 15.8%; ≥3 switches 13.0% vs 5.8%; p=0.01). The first biologic drug survival times of infliximab and adalimumab were significantly longer in the White British group compared to the South Asian group (South Asian vs. White British; median time on infliximab: 10 months vs. 26 months; p=0.032, median time on adalimumab; 9 months vs. undefined p=0.006; proportion of South Asian vs. White British group on adalimumab after 60 months; 27.3% vs. 57.4%). There were no significant differences in the first biologic drug survival times of etanercept and certolizumab between the two groups (White British vs. South Asian median time on etanercept: 50 months vs. 55 months; p=0.593; median time on certolizumab: 25 months vs. 13 months, p=0.860). There was no significant difference in the DAS28 score between the two groups after three months of biologic therapy [South Asian vs White British, median (IQR); 5.2 (4.2-6.1) vs 4.8 (3.4-6.0)]. Conclusions: Our data indicates that there are ethnic differences in the persistence of bDMARDs among patients with RA. This has clinical implications when determining the choice of biologic therapy for patients from different ethnic backgrounds. Disclosure of Interest: K. Kumar: None declared, I. Sahbudin: None declared, A. Filer Grant/research support from: Pfizer, C. D. Buckley: None declared, K. Raza Speakers bureau: K Raza has received honoraria from Pfizer, AbbVie and BMS., R. Stack: None declared, P. Nightingale: None declared, A. Deeming: None declared, D. Situnayake: None declared, P. de Pablo: None declared